Circle-seq reveals that eccDNA may be a key blood biomarker for HBV-associated liver cancer - Ran, Xiao K.; Zhao, Xiao F.; Wei, Zhen W.; Pang, Hua Z.; Tang, Yan F.; Liu, Rong; Wu, Tie X.; Liu, Xu D. (Frontiers in Genetics, 2025)
IntroductionExtrachromosomal circular DNA (eccDNA) regulates tumor occurrence and development. Relevant eccDNA profiles have been established for various types of cancer; however, the eccDNA expression profiles in the blood of patients with hepatocellular carcinoma (HCC) and liver cirrhosis (LC) remain unknown. The present study aimed to investigate the eccDNA expression profiles in the blood of patients with HCC and LC.MethodsCircle-seq was used to detect eccDNAs in the blood samples. Full transcript sequencing was used to analyze the RNA in the samples. Geno Ontology enrichment and Kyoto Encyclopedia of Genes and Genome pathway analyses were performed on differentially expressed eccDNA-related genes. The identified eccDNA is combined with mRNA to screen target genes using bioinformatics analysis. EccDNAs were confirmed through polymerase chain reaction and Sanger sequencing.ResultsOverall, 103,235 eccDNAs were identified in HCC, whereas 67,110 eccDNAs were detected in LC. In total, 7,095 upregulated eccDNAs and 1,284 downregulated eccDNAs were identified. Following analysis of differential genes using bioinformatics, six candidate genes were screened out based on gene expression and cancer relevance. Experiments have verified that LAMA4[circle112550019-112550510] and KANK1[circle674459-674907] are real and expressed target genes, and their source genes are closely related to the survival time of patients with liver cancer.ConclusionOur research results revealed the main characteristics of eccDNAs in the blood of patients with HBV-related HCC and LC. It was found that eccDNAs were mainly less than 1,000 bp in length. Difference analysis showed that some eccDNAs had consistent and overlapping expressions with mRNAs. We found that LAMA4[circle112550019-112550510] and KANK1[circle674459-674907] are target genes related to HCC, and both of them may become potential biomarkers for the diagnosis and prognosis of HCC.